Supplemental Material for "Genetic background of cow-human, cow-cow and cow-technical system behavior responses" - Behren, Larissa E.; Vanvanhossou, Sèyi Fridaïus U.; Breitmeier, Laura; Stuhlträger, Julia; Gieseke, Daniel; Rosner, Frank; Swalve, Hermann H.; König, Sven; Justus Liebig University Giessen (My University, 2026)
The data tables are supplemental material for the research article "Genetic background of cow-human, cow-cow and cow-technical system behavior responses". The supplementary data include 8 tables: - Supplemental Table S1. Least square means for categorical effects (AMS-herd and season) with corresponding SE for cow-human interaction traits - Supplemental Table S2. Regression coefficients (ß) of continuous effects for parity and DIM with corresponding SE on cow-human interaction traits - Supplemental Table S3. Least square means for categorical effects (AMS-herd and season) with corresponding SE for cow-cow interaction traits - Supplemental Table S4. Regression coefficients (ß) of continuous effects (parity and DIM) with corresponding SE on cow-cow interaction traits - Supplemental Table S5. Least square means for categorical effects (AMS-herd and season) with corresponding SE for cow-AMS interaction traits - Supplemental Table S6. Regression coefficients (ß) of continuous effects (parity and DIM) with corresponding SE on cow-AMS interaction traits - Supplemental Table S7. Least square means for categorical effects (AMS-herd and season) with corresponding SE for daily milking robot production traits - Supplemental Table S8. Regression coefficients (ß) for continuous effects (parity and DIM) with corresponding SE on daily milking robot production traits
Keywords: ddc:630